(untitled) (Journal of Economic Research & Business Administration, 2017)
Implementation of the priorities of mutual satisfaction within the EAEU demand for innovation and high-tech products creates a basis for the organizational and economic programming of the international competitiveness of science and technology complexes of EAEU member states in order to create new types of industries in the scientific and technological basis of strategic innovation programs pool. This requires a layout of complex processes of managing a large number of business units involved in the innovation processes that can be effectively structured under the concept of creating a Eurasian-allied networks of innovation clusters to form a new technological base using core market-shaping innovation through the implementation of a strategic pool of innovative programs.